Online buying and selling with Salam Contract in the consumption behavior of millennial youth - Fathimatuz Zahro; Mansur Chadi Mursid (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2022)
The era of globalization can be said to be the spread of habits that have become worldwide relationships in the social life on a larger scale, including in Indonesia, which is still in the category of developing countries. The current developing trend is buying and selling online, buying and selling online is a buying and selling transaction where the buyer must order first. In fiqh terms, it is called bay 'as-salam. This results in the occurrence of consumptive behavior, namely where a person's act of buying an item without any reasonable consideration that the person buying an item is not based on a need factor. This study aims to find out about buying and selling in the view of Islam, as well as the practice of buying and selling salam (orders) online and to find out the consumer behavior of millennial teenagers today. This study uses a qualitative method. The type of research used by the author is library research, a series of activities related to library data collection methods.